Approach to the humerus and femur of the paca (Cuniculus paca, Linnaeus 1766) - Leal, Leonardo Martins; Vasques, Gabriela Maria Benedetti; Sasahara, Tais Harumi de Castro; Vulcano, Luiz Carlos [UNESP]; Machado, Marcia Rita Fernandes [UNESP]; Minto, Bruno Watanabe [UNESP] (Wiley, 2021)
The paca (Cuniculus paca, Linnaeus 1766) is a rodent species, typical of tropical regions. It is important that in addition to its commercial value as a protein source, it can be used as a scientific scope. The objective of this study was to describe the morphology of the thigh and the arm of the paca by anatomical and imaging methodology with radiography (X-ray), computed tomography (CAT scan) and magnetic resonance imaging (MRI) to determine the surgical approach of the bones of these regions. It was concluded that the imaging study through X-ray, CAT scan and MRI are reliable methods for anatomical description of wild animals that have little known about their morphology. Finally, similarly to dogs, it was determined that lateral access is the best approach to the femoral diaphysis and the medial access is the best approach to the humerus diaphysis of the paca.
Keywords: computed tomography; fracture; magnetic resonance; orthopaedics; wild